(untitled) (Journal of Applied Oral Science, 2010)
Advances in all-ceramic systems have established predictable means of providing metal-free aesthetic and biocompatible materials. These materials must have sufficient strength to be a practical treatment alternative for the fabrication of crowns and fixed partial dentures. OBJECTIVES: The aim of this study was to compare the biaxial flexural strength of three core ceramic materials. MATERIAL AND METHODS: Three groups of 10 disc-shaped specimens (16 mm diameter x 1.2 mm thickness - in accordance with ISO-6872, 1995) were made from the following ceramic materials: Turkom-Cera Fused Alumina [(Turkom-Ceramic (M) Sdn Bhd, Puchong, Selangor, Malaysia)], In-Ceram (Vita Zahnfabrik, Bad Säckingen, Baden-Württemberg, Germany) and Vitadur-N (Vita Zahnfabrik, Bad Säckingen, Baden-Württemberg, Germany), which were sintered according to the manufacturer's recommendations. The specimens were subjected to biaxial flexural strength test in an universal testing machine at a crosshead speed of 0.5 mm/min. The definitive fracture load was recorded for each specimen and the biaxial flexural strength was calculated from an equation in accordance with ISO-6872. RESULTS: The mean biaxial flexural strength values were: Turkom-Cera: 506.8±87.01 MPa, In-Ceram: 347.4±28.83 MPa and Vitadur-N: 128.7±12.72 MPa. The results were analyzed by the Levene's test and Dunnett's T3 post-hoc test (SPSS software V11.5.0 for Windows, SPSS, Chicago, IL, USA ) at a preset significance level of 5% because of unequal group variances (P